Structure and bonding in crystalline materials - Rohrer, Gregory S. (Cambridge University Press, 2001)
How can elements be combined to produce a solid with specified properties? This book acquaints readers with the established principles of crystallography and cohesive forces needed to address the fundamental relationship among composition, structure and bonding. Starting with an introduction to periodic trends, the book discusses crystal structures and the various primary and secondary bonding types, and finishes by describing a number of models for predicting phase stability and structure. Its large number of worked examples, exercises, and detailed descriptions of numerous crystal structures make this an outstanding advanced undergraduate or graduate-level textbook for students of materials science.